Continuing Effectiveness of Serogroup A Meningococcal Conjugate Vaccine, Chad, 2013 - Gamougam, Kadidja; Daugla, Doumagoum M.; Toralta, Jacques; Ngadoua, Cyriaque; Fermon, Florence; Page, Anne-Laure; Djingarey, Mamoudou H.; Caugant, Dominique A.; Manigart, Olivier; Trotter, Caroline L.; Stuart, James M.; Greenwood, Brian M. (Emerging infectious diseases, 2015)
In 2011, vaccination with a serogroup A meningococcal polysaccharide conjugate vaccine was implemented in 3 of 23 regions in Chad. Cases of meningitis declined dramatically in vaccinated areas, but an epidemic continued in the rest of Chad. In 2012, the remaining Chad population was vaccinated, and the epidemic was halted.